The Effect of Mergers and Acquisitions on Employees: Wealth Transfer, Gain‐Sharing or Pain‐Sharing?. (5th November 2019) - Kuvandikov, Azimjon; Pendleton, Andrew; Higgins, David
Abstract: This paper considers whether gains made by shareholders from corporate takeovers are achieved at the expense of employees, as proposed by the 'wealth transfer' perspective. It analyses the contribution of employee lay‐offs, along with employment and wage changes, to the takeover premium and abnormal share price movements. The analysis draws on a unique dataset of British takeovers, combining documentary, share price and accounting data. The results show that lay‐offs planned at the takeover have either no effect or adverse effects on shareholder returns. Wages growth is positively, not inversely, related to shareholder returns from the second year after the takeover, whilst positive employment changes have a similar effect in the following year. Closer scrutiny indicates that labour and shareholders share gains when the firm does well, but share pain when it does not. There is evidence, therefore, that labour and shareholder interests can be complementary, rather than antagonistic, after takeovers.